Urinary bisphenol A levels in Turkish girls with premature thelarche. (October 2018) - Durmaz, E; Asci, A; Erkekoglu, P; Balcı, A; Bircan, I; Koçer-Gumusel, B
There is a growing concern over the timing of pubertal breast development and its possible association with exposure to endocrine disrupting chemicals (EDCs), such as bisphenol A (BPA). BPA is abundantly used to harden plastics. The aim of this study was to investigate the relation between premature thelarche (PT) and BPA by comparing the urinary BPA levels of PT girls with those of healthy subjects. Twenty-five newly diagnosed nonobese PT subjects (aged 4–8 years) who were admitted to the Pediatric Endocrinology Department at Akdeniz University were recruited. The control group composed of 25 age-matched girls without PT and other endocrine disorders. Urinary BPA levels were measured by high pressure liquid chromatography. The median urinary concentrations of BPA were found to be significantly higher in the PT group compared to the healthy control group (3.2 vs. 1.62 μg/g creatinine, p < 0.05). We observed a weak positive correlation between uterus volume and urinary BPA levels. There was a weak correlation between estradiol and urinary BPA levels ( r = 0.166; p = 0.37); and luteinizing hormone and urinary BPA levels ( r = 0.291; p = 0.08) of PT girls. Our results suggest that exposure to BPA might be one of the underlying factors of early breast development in prepubertal girls and EDCs may be considered as one of the etiological factors in the development of PT.